A field study on hydrological impacts of an eco-construction in a small catchment area located near the city of Yan an in the Loess Plateau of China - Xu,Xuexuan; Tian,Junliang; Liu,Puling; Söderlund, Leif (MTT, 2005)
This paper is based on the findings of a field study performed from 2002 to 2003 near the city of Yan an, which is in a gullied hilly region of the loess plateau of China. The two-year system survey monitored the temporal and spatial distribution of rainfall, soil moisture, underground flow (springs), and overflow in the Kang gou catchment in the Yan gou watershed near Yan an. The authors analysed the inner mechanism of interaction between rainfall, soil moisture, underground flow and runoff modules by comparing the values of these parameters in order to understand the hydrological responses in an eco-construction project. The results show that the eco-construction did not cause a decrease in runoff in heavy rainfall but could fully absorb lowintensity rainfall of long duration. The soil moisture increased along with downside slope, and spring flow increased with higher soil water content too. When runoff happened, spring flow sometimes would increase for the next 3 10 days. In general, the purpose of eco-construction in the loess plateau is to enable sustainable water use, which is very necessary to implement the region s ongoing Land Use and Cover Change (LUCC) projects including reforestation and grassland restoration.
Keywords: Ys; hydrologiset vaikutukset; Kiina; ekologinen rakentaminen; valuma-alueet; hilly loess region; eco-construction; hydrological impacts; small catchment; field study; kenttätutkimus